Media Flipbooks Terintegrasi Edmodo Mikrobiologi Sebagai Upaya Pemberdayaan Kemampuan Metakognisi Mahasiswa di Masa Pandemi Covid-19 - Purwaning Budi Lestari; Mistianah Mistianah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2020)
The purpose of this study is to recognize the application of flipbooks maker integrated Edmodo in the course of microbiology in empowering the student metacognitve ability in the covid-19 pandemy. The research method used Classroom Action Research. The subjects of the study were biology students of IKIP Budi Utomo at class B 2017. Instrument of the research consisted of semester learning plan of microbiology, test with Cognitive 5 category; rubric of metacognitive ability; and questionnaire of learning feedback. Data collection techniques used observation sheet and a special metakognitive ability test integrated with essay test with a score range of 1-7. The data analysis technique used qualitative descriptive analysis. The results of research showed that in cycle I the highest score reached level 6 of 21.5%, while in cycle II the highest score reached level 7 amounted to 39.8%. Meanwhile, the average score increased in cycle I, i.e. the ability of students’ metacognitive was 65,5 and cycle II amounted to 83.6. Thus, it can be concluded that the Flipbooks maker integrated Edmodo can empower the students metacognitive ability in the microbiology learning in the Covid-19 pandemic.